Black November: Interrogating The Niger Delta Question - anyanwu, chukwuma (The Journal of Society and Media, 2021)
The paper interrogates the thematic preoccupations of Jeta Amatas Black November on the vexed issues of the Niger Delta in Nigeria. The issues bordering on the quest for emancipation from injustice, environmental degradation, deprivation, inhuman treatment, negligence, are at the nexus of the agitations and militancy in the region. It draws inferences from what the movie overlooked and what it portrayed such as the failure of dialogue births violence. The objective is to highlight the problems in the Niger Delta and give credence to the thematic concerns raised by the director. Based on Relative Deprivation Theory (RDT), which sees violence as a product of frustration borne out of depriving people of their rights, denial of justice; a sense of oppression sets in that then leads to reactions that may be violent. The method adopted is descriptive analysis. Findings reveal that the Niger Delta region is much misunderstood, abused and betrayed by its own people, the media, Nigerian government, oil multinationals and the world at large. It concludes that the misunderstanding is largely a product of media misinformation and that of ignorance on the part of stakeholders and that the filmmaker succeeded in getting his message across.